The Benedictines of Jezow. Establishing a monastery and the activity of monks in the Renaissance era - z Stolarczyk, Tomasz (Jakub Przyłuski (1512–1554): Outline of life and literary work against the background of the epoch, 2022)
The article consists of 3 main parts. In the first, the issue of the erection of the Benedictine provostry of Jezow in the 12th century was discussed. In the second, the endowment of the monastery in Jezow was discussed. The third section presents the history of this provostry in the 13th–16th centuries.